2014
DOI: 10.1016/j.pmatsci.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor-based ferroelectric single crystals: Growth, domain engineering, characterization and applications

Abstract: In the past decade, domain engineered relaxor-PT ferroelectric single crystals, including (1-x)Pb(Mg1/3Nb2/3)O3-xPbTiO3 (PMN-PT), (1-x)Pb(Zn1/3Nb2/3)O3-xPbTiO3 (PZN-PT) and (1-x-y)Pb(In1/2Nb1/2)O3-yPb(Mg1/3Nb2/3)O3-xPbTiO3 (PIN-PMN-PT), with compositions near the morphotropic phase boundary (MPB) have triggered a revolution in electromechanical devices owing to their giant piezoelectric properties and ultra-high electromechanical coupling factors. Compared to traditional PbZr1-xTixO3 (PZT) ceramics, the piezoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
264
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 519 publications
(283 citation statements)
references
References 449 publications
3
264
0
3
Order By: Relevance
“…Recently, Zhang et al and Sun et al [2][3][4] demonstrated that the Pb(Zn1/3Nb2/3)0.91Ti0.09O3 (PZN-9PT) crystal exhibits an exceptionally large piezoelectric constant (d33 > 2000 pC/N) and electromechanical coupling factor in longitudinal bar mode (k33 > 92%). These properties are expected to be applied in high-quality piezoelectric devices, such as medical ultrasonic transducers, actuators, and sonars, as replacements for conventional PZT ceramics [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang et al and Sun et al [2][3][4] demonstrated that the Pb(Zn1/3Nb2/3)0.91Ti0.09O3 (PZN-9PT) crystal exhibits an exceptionally large piezoelectric constant (d33 > 2000 pC/N) and electromechanical coupling factor in longitudinal bar mode (k33 > 92%). These properties are expected to be applied in high-quality piezoelectric devices, such as medical ultrasonic transducers, actuators, and sonars, as replacements for conventional PZT ceramics [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…В этих монокри-сталлических твердых растворах с составами вблизи морфотропной фазовой границы (МФГ) наблюдаются ультравысокие значения пьезоэлектрических коэффици-ентов (1500−2500 pC/N) и коэффициентов электромеха-нической связи (> 0.9) [4][5][6]. МФГ в системе PMN−xPT (27 < x < 35%) разделяет две сегнетоэлектрические фазы: ромбоэдрическую (R), в которой спонтанная поля-ризация ориентирована вдоль направления [111], и тет-рагональную (T ) с направлением спонтанной поляриза-ции вдоль [001].…”
Section: Introductionunclassified
“…A high electromechanical coupling factor is suitable for the design of ultrawideband SAW filters [2][3][4]. Relaxor based ferroelectric single crystals, such as Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 (PMNT or PMN-xPT) and Pb(Zn 1/3 Nb 2/3 )O 3 -xPbTiO 3 (PZNT or PZN-xPT), have ultrahigh electromechanical coupling factor 33 (>94%) and piezoelectric constant 33 (>2500 pC/N) near the morphotropic phase boundary at room temperature [5][6][7][8][9]. However, PMNT single crystals have low Curie temperature ( c ≈ 130 ∘ C) and phase transition temperature ( rT ≈ 85 ∘ C); these characteristics limit their applications under high temperatures.…”
Section: Introductionmentioning
confidence: 99%